ENHANCING IPE FACILITATOR CAPACITY: A TRAINING PROGRAM ON UTILIZING THE RESPECT QUESTIONNAIRE TO EVALUATE INTERPROFESSIONAL REFLECTION ABILITY - Ameli Dwi Fitri; Anggelia Puspasari; Citra Maharani; Rina Nofri Enis; Erny Kusdiyah; Wahyu Indah Dewi Aurora; Nyimas Natasha Ayu Shafira; Herlambang (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
ABSTRACT Interprofessional Education (IPE) is a mandated learning process to prepare "collaborative practice-ready" healthcare professionals. This community service aimed to enhance the capacity of teaching staff at the Faculty of Medicine and Health Sciences (FKIK) Jambi University (UNJA) as competent IPE facilitators, especially in evaluating students' interprofessional reflection abilities using the validated RESPECT instrument]. The training method was applied through lectures, discussions, and role-playing on giving constructive feedback. The activity successfully delivered material on reflection instruments and facilitator competencies to the target of 30 teaching staff. Facilitators were trained to be role models who emphasize reflection at both the professional and interprofessional levels, which is crucial for building a strong collaborative mindset and overcoming prejudices between professions. The result of this community service is a targeted increase in faculty capacity to assess student reflection, ensuring IPE implementation supports the creation of comprehensive healthcare services. Keywords: Collaboration, Facilitator, Interprofessional Education, Reflection, RESPECT